ANALISIS PERTUMBUHAN EKONOMI PENGGUNA INTERNET DAN KONSUMSI ENERGI LISTRIK DI INDONESIA - Rani Gusminda Putri; Idris Idris (Universitas Negeri Padang, 2021)
This study aims to identify and analyze the response between economicgrowth, internet users, and consumption of electrical energy in Indonesia. This type of research is descriptive and associative, the data used are secondary panel data from 2016 to 2020. This research was conducted using the Vector Autoregression (VAR) model through the analysis of Impulse Response Funtion (IRF) and Variance Decomposition (VD) to determine the variability response of a particular variable due to the shock of other variables. The results of this study indicate that: (1) Variability of econmic growth is not contributed by internet users in the short term, but in the long term variability of economic growth is contributed by the shock of internet users in Indonesia, (2) Variability internet users is contributed by economic growth in short and long term,(3) Variability internet users in short term is not contibuted by consumption of electrical energy , but in long term is contrubuted by the consumption of electrical energy in Indonesia, (4) Variability consumption of electrical energy in short term and long term is contributed by internet users in Indonesia, (5) Variability consumption of electrical energy in short term and long term is contributed by economic growth in Indonesia, (6) Variability econmic growth is contributed by the consumption of electrical energy ionlyin the long term.